2013
DOI: 10.1530/eje-13-0228
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with severe hypothyroidism

Abstract: Objective: Hypothyroidism during pregnancy has been associated with adverse obstetrical outcomes. Most studies have focused on subjects with a mild or subclinical disorder. The aims of the present study were to determine the relative rate of severe thyroid dysfunction among pregnant women with hypothyroidism, identify related factors and analyse the impact on pregnancy outcomes. Design: A retrospective case series design was employed. Methods: The study group included 101 pregnant women (103 pregnancies) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
0
30
1
4
Order By: Relevance
“…In a study conducted by Hirsch et al premature deliveries was found to be 2.9% in clinical hypothyroid women [10] . Preterm deliveries were found to be higher in studies by Kumru and Nazarpour et al in studies conducted in Turkey and Iran respectively.…”
Section: Discussionmentioning
confidence: 94%
“…In a study conducted by Hirsch et al premature deliveries was found to be 2.9% in clinical hypothyroid women [10] . Preterm deliveries were found to be higher in studies by Kumru and Nazarpour et al in studies conducted in Turkey and Iran respectively.…”
Section: Discussionmentioning
confidence: 94%
“…9,10 In a study conducted by Hirsch et al premature deliveries were found out to be 2.9% in clinical hypothyroid. 11 The prevalence of low birth weight babies (birth weight less than 2.5 kg) in group A is found to be 10%. And the prevalence of preterm babies in group B is 22%.…”
Section: Discussionmentioning
confidence: 96%
“…Despite those, several reports of severe OH did not show an increased rate of pregnancy-related complications, suggesting that even severe hypothyroidism does not necessarily preclude normal pregnancy outcomes nor induce complications (37).…”
Section: Evidence For Adverse Effects Of Sch During Pregnancymentioning
confidence: 94%